Key agreement for heterogeneous mobile ad-hoc groups. (15th January 2010) - Manulis, Mark; Sadeghi, Ahmad-Reza
Security of various group-oriented applications for mobile ad-hoc groups requires a group secret shared between all participants. Contributory Group Key Agreement (CGKA) protocols can be used in mobile ad-hoc scenarios due to the absence of any trusted central authority (group manager) that actively participates in the computation of the group key. Members of spontaneously formed mobile ad-hoc groups are usually equipped with different kinds of mobile devices with varying performance capabilities. This heterogeneity opens new ways for the design of CGKA protocols and states additional security requirements with regard to the trustworthiness of the devices. In this paper we propose a CGKA protocol for mobile ad hoc groups that fairly distributes the computation costs amongst mobile devices by taking into account their performance limitations and preventing possible cheating through Trusted Computing techniques.